(untitled) (Community Based Medical Journal, 2016)
Placenta percreta is a rare condition and extremely rare in first trimester of pregnancy. It is a life threatening obstetric condition specially in undiagnosed cases. Here we report a case of 32 years 5th gravid woman having history of previous one caesarian section(C/S) and two dilatation and curettage (D&C), who presented to us with life threatening vaginal bleeding during the attempt of curettage of 12 weeks missed pregnancy. Along with resuscitation emergency hysterectomy was done. Placenta was found in lower segment of uterus invading up to serous coat. Histopathology also confirmed placenta percreta. She received 6 units of blood. She was discharged from hospital after 7 days in good health. CBMJ 2016 January: Vol. 05 No. 01 P: 46-49